Citrus/Cydonia Comp. Can Restore the Immunological Balance in Seasonal Allergic Rhinitis-Related Immunological Parameters In Vitro - E. W. Baars; H. F. J. Savelkoul (Mediators of Inflammation)
In two in vitro studies, we examined the immunological (pathways of the) effects of Citrus/Cydonia comp. from, respectively, a healthy and an allergic donor; peripheral blood mononuclear cells (PBMCs) were isolated out of peripheral blood and analyzed in vitro after polyclonal stimulation of T-cells. The differentiation capacity and the influence with regard to Th1 (IFN-γ) and Th2 (IL-5) cells were examined. Citrus/Cydonia comp. has a selective effect on the differentiation of T-cells by producing relatively more IL-10 than IL-12. By that, it also seems to have an effect on the induction of regulatory (IL-10 producing) T-cell subsets. It is in vitro capable of neutralizing (to some extent) the changes, characteristic to allergic rhinitis, with regard to the maturation, differentiation, and activity of the immune system. Thus, Citrus/Cydonia comp. can potentially restore the disturbed immune state of rhinitis patients, which essentially could be sufficient to make allergic symptoms disappear permanently.